Teaching by Production Rather Than Products - Loewen, Nathan (Method & theory in the study of religion, 2016)
The classroom has potential to be the most common context for the dissemination of method and theory in religious studies. Scholars have the ability to perform scholarly competencies in their teaching venues such as providing evidentiary support, taking stock of methodological concerns, and demonstrating familiarity with current trends in criticism within the field, just to name a few. Those who take seriously critical moves in the field, furthermore, might see the dialogical self-consciousness and an attention to structures to be shared primary interests for critical theory and contemporary pedagogy. All too often, and problematically, the competencies applied in scholarship are separated from teaching. Research is seen as “real work” (e.g., publications and conference papers) and, for many, teaching merely serves those practical ends. With this problematic dichotomy in mind, the publishing of The Norton Anthology of World Religions (nawr) is sadly not surprising in the year 2015. When critical scholarship is withheld from pedagogical tools (like an anthology), the demonstrable lack of scholarly competency and disciplinary aptitude in Jack Miles’ preface and introduction to the nawr remains unremarkable (particularly since he claims to address religious studies undergraduates and their professors). Miles not only presents the nawr as a means by which “international world religions should be allowed to speak to you in their own words” (Miles 2015: li) but he also prescribes—as supposedly prior to theoretical commitments—the method of “secular, neutral comparative study of religion” (41) through the “fine art of page flipping” (lvii) as the original and best practice for the study of religion. Miles’ failures as a critic and as a pedagogue merely reflect the presumption that students need only interact with the superstructures of higher education and not be let in on the processes that create scholarship. This essay will outline this problematic vis-à-vis the preface and introduction to the nawr in order to highlight the role a critical study of religion should play in our teaching.